Intimate crimes : kidnapping, gangs, and trust in Mexico City - Ochoa Hernandez, Rolando, 1975- (Oxford : Oxford University Press, 2019)
This is an authoritative history of kidnapping based on extensive qualitative research of gangs and policing, as well as an analysis of the effect the crime has on how communities experience the city, and the strategies put in place by potential victims to avoid the threat of kidnapping.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 14, 2019).
Keywords: Kidnapping -- Mexico -- Mexico City